Molecular Characterization of Prdx Family and Response of Antioxidant Enzymes in Berberine Hydrochloride-Treated Charybdis japonica Infected With Aeromonas hydrophila - Han, Mingming; Gao, Tianheng; Liu, Yuxin; Zuraini, Zakaria; Zhu, Chenxi; Zhang, Tongqing; Ji, Feng; Jiang, Qichen; Sun, Xian (Frontiers in Marine Science, 2021)
Berberine hydrochloride is an isoquinoline alkaloid, which has antitumoral, antibacterial, and antiviral activities in vivo and in vitro. Charybdis japonica is one of the main economic species of crab in Southeast Asia. We studied the molecular mechanism of oxidative stress in berberine hydrochloride-treated C. japonica infected with Aeromonas hydrophila. C. japonica were infected with A. hydrophila after being submerged in different concentrations (0, 100, 200, and 300 mg/L) of berberine hydrochloride for 48 h. The full-length cDNA of Prx6 and the ORFs of Prx5 and PXL2A were cloned. Prx6 and PXL2A each have one conserved domain, Cys44, and Cys81. The Prx5 conserved domain contains three important Cys loci, Cys75, Cys100, and Cys76. Prx6 was different from Prx5 and PXL2A in the Peroxiredoxin family. The transcription levels of PXL2A infected with A. hydrophila were all higher than the control. The transcription levels of C. japonica were further increased by adding berberine hydrochloride and were increased the highest at a concentration of 300 mg/L. The activities of glutathione peroxidase, superoxide dismutase, and catalase in the hepatopancreas of berberine hydrochloride-treated C. japonica infected with A. hydrophila were significantly increased compared with those only infected with A. hydrophila and the control group. The glutathione transferase activity in the hepatopancreas was significantly increased in berberine hydrochloride-treated C. japonica. The results of this study provide a new understanding of the potential role of berberine hydrochloride on the oxidative stress mechanisms of C. japonica.